Weather-based index insurance for climate risk management in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Despite government subsidies, many farmers remain uninsured and dissatisﬁed with current insurance products. In the case of weather-based index insurance, spatial variability of weather, lack of historical data to develop appropriate insurance triggers at local level, and poor insurance delivery systems are the major constraints. CCAFS South Asia is working with the Agriculture Insurance Company of India to help them design insurance schemes that are better suited to farmers’ need in different locations.